Multislice CT angiography in the diagnosis of coronary artery disease - Sun, Zhonghua; Cao, Y.; Li, H. (Science Press, 2011)
Multislice CT angiography represents one of the most exciting technological revolutions in cardiac imaging and it has been increasingly used in the diagnosis of coronary artery disease. Rapid improvements in multislice CT scanners over the last decade have allowed this technique to become a potentially effective alternative to invasive coronary angiography in patients with suspected coronary artery disease. High diagnostic value has been achieved with multislice CT angiography with use of 64- and more slice CT scanners. In addition, multislice CT angiography shows accurate detection and analysis of coronary calcium, characterization of coronary plaques, as well as prediction of the disease progression and major cardiac events. Thus, patients can benefit from multislice CT angiography that provides a rapid and accurate diagnosis while avoiding unnecessary invasive coronary angiography procedures. The aim of this article is present an overview of the clinical applications of multislice CT angiography in coronary artery disease with a focus on the diagnostic accuracy of coronary artery disease; prognostic value of coronary artery disease with regard to the prediction of major cardiac events; detection and quantification of coronary calcium and characterization of coronary plaques. Limitations of multislice CT angiography in coronary artery disease are also briefly discussed, and future directions are highlighted.